The Main Macroeconomic Indicators of the Development of the European Union - Kuznetsova, Natalia Victorovna; Tarabukina, Anna Andreevna (Indian Journal of Finance, 2014)
The main objective of the paper was to conduct an analysis of the main macroeconomic indicators of the European Union member countries in the current economic scenario. The article showed the leaders of the EU by the economic strength: Germany, the United Kingdom, France, Italy, and Spain; they, in particular, define the tendencies and the structure of the Union's economy. The characteristics of the North Western European countries are also discussed. The EU countries, with transition economies, are distinguished by the high growth of macroeconomic indicators: they are leading in the GDP and GPD per capita growth rates in a 10-year period since 2003. The paper also showed that the European Union is an association of the national economies that effectively interact with each other.